Pengembangan Sistem Inventory Control Perusahaan Berbasis Web Studi Kasus PT. XYZ - Muhammad Al Anis Faishal; Tri Astoto Kurniawan; Denny Sagita Rusdianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
In conducting logistics activities every day, PT. XYZ uses 2 Inventory Control Systems, that are internal and external Inventory Control Systems. The Internal Inventory Control System is a purchased system from software developers. Then, the External Inventory Control is a leased system of a Electronic Data Interchange (EDI) services company in Indonesia every month that can be accessed by the Directorate General (DG) of Customs and Excise, as there is a Regulation of the DG of Customs and Excise No. per-09 / BC / 2014 CHAPTER II Article 2 Section 1, every company that uses Bonded Zone facilities must have IT Inventory accessible to the DG of Customs and Excise. Because PT. XYZ has 2 Inventory Control Systems, the logistics staff should enter the same data twice into both systems. So we need a good Inventory Control System that can be used internally and externally, that is a Web-based Inventory Control System, the result of a combination of internal and external Inventory Control Systems to be able to solve the problems of PT. XYZ right now. Web-based Inventory Control System, the result of a combination of internal and external Inventory Control System has been tested by unit testing and integration testing of 3 sample methods from several classes using white-box testing method get 100% valid results. Then, system testing by testing 85 functional requirements using black-box testing method get 100% valid results.